2022
DOI: 10.1002/adfm.202203430
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of MXene‐Integrated Composites: Regenerative Medicine, Infection Therapy, Cancer Treatment, and Biosensing

Abstract: MXenes (viz., transition metal carbides, carbonitrides, and nitrides) have emerged as a new subclass of 2D materials. Due to their outstanding physicochemical and biological properties, MXenes have gained much attention in the biomedical field in recent years, including drug delivery systems, regenerative medicine, and biosensing. Additionally, the incorporation of MXenes into hydrogels has garnered significant interest in biomedical engineering as an electroactive and mechanical nanoreinforcer capable of conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(37 citation statements)
references
References 190 publications
(294 reference statements)
0
37
0
Order By: Relevance
“…Numerous nanostructures with photothermal conversion capabilities have unique qualities, and many nano/biomaterials have been produced for PTT-based cancer therapy. [122][123][124][125][126][127][128] Although PTT has been widely used to treat cancer, it still has significant obstacles, including, inadequate tumor cell targeting, restrictions to surface tumors, and cancer recurrence. [121] Fortunately, combining PTT with other modalities such as photodynamic therapy (PDT), IT, gene therapy, and chemodynamic treatment could reduce such obstacles while maximizing the benefits of each therapeutic mode.…”
Section: Sdt-enhanced Photothermal Therapymentioning
confidence: 99%
“…Numerous nanostructures with photothermal conversion capabilities have unique qualities, and many nano/biomaterials have been produced for PTT-based cancer therapy. [122][123][124][125][126][127][128] Although PTT has been widely used to treat cancer, it still has significant obstacles, including, inadequate tumor cell targeting, restrictions to surface tumors, and cancer recurrence. [121] Fortunately, combining PTT with other modalities such as photodynamic therapy (PDT), IT, gene therapy, and chemodynamic treatment could reduce such obstacles while maximizing the benefits of each therapeutic mode.…”
Section: Sdt-enhanced Photothermal Therapymentioning
confidence: 99%
“…Electronic [145,154] Gas sensors, [155][156][157] tactile sensors, [158][159][160] biosensing, [65,161] field-effect transistors [162,163] Magnetic [164][165][166] Spintronics and quantum computing [167,168] Mechanical [146,169] Mechanical reinforcing material, [89,170,171] polymer composites [172][173][174] Optical and photonic [146,175] TCO, [176] saturable absorber, [152,177,178] mode-locked laser [177,179] Electromagnetic [180] Electromagnetic interference shielding [181,182] Thermoelectric [183][184][185] Thermoelectric electricity production [152,184,186] Chemical [187,188] Environmental stability, [189][190][191] batteries and supercapacitors, …”
Section: Properties Applicationsmentioning
confidence: 99%
“…Recently, MXenes have exhibited promising potential in the area of regenerative medicine and tissue engineering based on their high hydrophilicity, biodegradability, sorption selectivity, thermal/electrical conductivity, chemical stability, biocompatibility, and antibacterial activity. Some studies have shown that multilayered Ti 3 C 2 T x MXene films could upregulate the osteoblast-related gene expression in preosteoblasts, boost cell adhesion and proliferation in vitro , and promote early osteogenesis, mineralization, and bone regeneration in a rat calvarial defect model. , Additionally, the Ti 3 C 2 T x MXene addition could increase the mechanical properties, flexibility, and electrical conductivity of hydrogels, improve the proliferation activity in cells, and also enhance the soft tissue wound healing procedure. Therefore, 2D MXene and 2D MXene-based materials have received more attention in bone and soft tissue regeneration. , However, most of the previous reports focused on the fabrication and performance of MXene-based biomaterials and their inherent bioactivity, and the potential mechanism of pure MXene nanosheets in bone and soft tissue regeneration was paid little attention.…”
Section: Introductionmentioning
confidence: 99%